Development of a prosthetic arm with gesture recognition for enhanced social interaction - Bhuvaneswari, Thangavel; Soe, Min Thu; BC, Yeo; WS, Lim; Latief, Wildan; Wikanjaya, Rio; Canintika, Anissa Feby; Hutami, Witantra Dhamar; Alhuraebi, Ali Saleh; Hakim, Manfaluthy; et al. (Edelweiss Applied Science and Technology, 2025)
This paper presents the design and development of an affordable prosthetic arm capable of performing finger movements, such as opening and closing, in various patterns. The prosthetic arm utilizes an Arduino microcontroller and servo motors, aiming to create a user-friendly assistive device for individuals with upper limb disabilities through a Brain-Computer Interface (BCI). The device is intended for individuals with below-elbow (transradial) amputations, which may result from causes like trauma, cancer, or vascular diseases. Constructed with PLA+ materials, the prosthetic is designed for both comfort and durability, with 3D printing enabling cost-effective and customizable production. The prototype is tested for three movement patterns: default option 1: opening and closing all fingers starting from the pinky, option 2: opening and closing all fingers simultaneously, and option 3: opening and closing all fingers starting from the thumb. Test results are analyzed to evaluate the functionality and performance of the device. This innovative approach demonstrates the potential of a low-cost, highly functional prosthetic arm that can enhance mobility and independence for users, demonstrating the power of accessible, affordable technology for assistive applications.